Pelatihan Penyusunan Modul Ajar Berbasis Kurikulum Merdeka bagi Guru MGMP Biologi SMA di Kabupaten Brebes - Roshayanti, Fenny; Nizaruddin, Nizaruddin; Sumarno, Sumarno; Murtianto, Yanuar Hery; Muhtarom, Muhtarom (Perkumpulan Kualitama Edukatika Indonesia, 2023)
Curriculum development and its implementation in the classroom requires the full support of teachers for its implementation to be successful. The teacher is an important aspect in the process of developing and implementing the curriculum. For this purpose, teachers need to provide ongoing training that enables them to become more professional and better understand the independent curriculum. This service activity was carried out for MGMP Biology teachers at Brebes Regency High School. The method of implementing community service is carried out through three stages, namely: the preparation stage, the implementation stage and the evaluation stage. The training was carried out using an andragogy approach, where the training consisted of more demonstrations, questions and answers and practice as well as mentoring. The training material is presented with more practice than theory, with a ratio of 25% theory and 75% practice. The evaluation stage is carried out by giving a response questionnaire to evaluate community service activities. Service activities have been able to increase understanding and mastery of the independent curriculum. This is evidenced by the results of the activity showing an increase of 21.50% of the participants' knowledge after participating in the activity. The output of this service is scientific articles published in the Pelita Journal and publications in online media.